The attitudes of the contemporary Poles towards the archaeological past - Pawleta, Michał (Folia Praehistorica Posnaniensia, 2021)
This paper aims to present how the past is viewed in contemporary cultural and social narratives, and defines contemporary attitude to the past among Poles. My deliberations are placed in the context of the present-day society/culture and their constituting processes, namely the phenomenon of forgetting the past, democratization of the past, its privatization/individualization, commodification of the past and new ways of experiencing it. The paper will specifically concentrate on the archaeological past - that is the past created by archaeologists, and on archaeological heritage. It address three crucial issues, namely: (1) how changes in the historical context of post-1989 Poland influenced the emergence the renaissance of the past and different narratives about it; (2) what are the most important and widespread forms of presenting and/or experiencing the archaeological past in the present?, and (3) what are the main motivations that lie behind contemporary Poles interest in the past, archaeological heritage and activities undertaken around it? Finally, it is argued that the changes in the people’s attitudes towards the past have led also to a transformation in the hierarchy of aims and methods in education and dissemination of the knowledge about the past within institutions concerned with the past on a professional level.